1980
DOI: 10.1007/bf01855841
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cimetidine upon gastric secretion and mucosal blood flow in the rat stressed by restraint

Abstract: The effect of the histamine-H2-receptor blocking agent cimetidine (CT) on gastric secretion, mucosal blood flow (MBF), and gastric mucosal stress ulcer index was studied in rats (n = 96) during control conditions (3.9, 15.6, 62.4 microMol/kg/h CT i.p. over 8 h) with calculation of kinetic constants (Vmax; Km) for gastric secretion, MBF and ulcer index, it is shown that CT actions become considerably modified by severe stress. Under mild stress the reduction of MBF and acid secretion by increasing CT doses is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1981
1981
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Key Words: gastric mucosal lesions, lipid peroxidation, microcirculation, thiobarbituric acid-reactive substances, water-immersed restraint stress Several pathogenetic mechanisms have been suggested to account for stressinduced gastric mucosal lesions: disturbance of gastric mucosal microcirculation [1][2][3][4][5], alteration in gastric secretion [2,6], abnormal gastric motility [7], and hyperacidity [6].…”
Section: Discussionmentioning
confidence: 99%
“…Key Words: gastric mucosal lesions, lipid peroxidation, microcirculation, thiobarbituric acid-reactive substances, water-immersed restraint stress Several pathogenetic mechanisms have been suggested to account for stressinduced gastric mucosal lesions: disturbance of gastric mucosal microcirculation [1][2][3][4][5], alteration in gastric secretion [2,6], abnormal gastric motility [7], and hyperacidity [6].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, much data has indicated that the mechanisms of SGMI have been implicated in the pathogenesis of increase in gastric acid and pepsin secretion, a decrease in gastric mucosal blood flow, inhibition of endogenous generation of prostaglandins, increased generation of reactive oxygen species, suppression of gastric mucosal cell growth and proliferation (Das and Banerjee, 1993;Hemmer et al, 1980;Konturek et al, 1990). However, little is known about the role of the central nuclei in regulating SGMI.…”
Section: Introductionmentioning
confidence: 97%
“…At present, the cellular and molecular mechanisms involved in gastric mucosal defense against gastrodamaging factors are well known (Wallace and Granger, 1996). Several aggressive mechanisms have been implicated in the pathogenesis of stress ulcers, including increased secretion of gastric acid and pepsin and increased generation of reactive oxygen species (Das and Banerjee, 1993;Hemmer et al, 1980;Konturek et al, 1990). However, the mechanisms underlying the mucosal damage mediated by aggressive factors remain elusive.…”
Section: Introductionmentioning
confidence: 98%